2017
DOI: 10.1038/srep45238
|View full text |Cite
|
Sign up to set email alerts
|

Novel Model of Tendon Regeneration Reveals Distinct Cell Mechanisms Underlying Regenerative and Fibrotic Tendon Healing

Abstract: To date, the cell and molecular mechanisms regulating tendon healing are poorly understood. Here, we establish a novel model of tendon regeneration using neonatal mice and show that neonates heal via formation of a ‘neo-tendon’ that differentiates along the tendon specific lineage with functional restoration of gait and mechanical properties. In contrast, adults heal via fibrovascular scar, aberrant differentiation toward cartilage and bone, with persistently impaired function. Lineage tracing identified intri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
324
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 205 publications
(364 citation statements)
references
References 68 publications
17
324
1
1
Order By: Relevance
“…By contrast, we have never observed HO following injury of wild-type skeletal muscle, despite the well-documented presence of interstitial osteocompetent cells[38,64,65]. Additionally, tendons of neonatal mice are refractory to injury-induced HO[66]. Whether these differences in HO susceptibility represent key age- and tissue-specific differences in the signaling/inflammatory environments, bioavailability of osteogenic ligands, or susceptibility of distinct stem/progenitor populations remains to be clarified.…”
Section: Animal Models Of Heterotopic Ossificationmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, we have never observed HO following injury of wild-type skeletal muscle, despite the well-documented presence of interstitial osteocompetent cells[38,64,65]. Additionally, tendons of neonatal mice are refractory to injury-induced HO[66]. Whether these differences in HO susceptibility represent key age- and tissue-specific differences in the signaling/inflammatory environments, bioavailability of osteogenic ligands, or susceptibility of distinct stem/progenitor populations remains to be clarified.…”
Section: Animal Models Of Heterotopic Ossificationmentioning
confidence: 99%
“…Howell et al[66] observed that Scx-expressing cells give rise to cartilage following tendonectomy. Similarly, Scx-lineage-labeled cells accounted for ~40% of definitive cartilage and ~25% of definitive intratendinous bone following burn/tendonectomy[94].…”
Section: Progenitors Of Heterotopic Ossificationmentioning
confidence: 99%
“…Strikingly little is known regarding the actual mechanisms by which originally healthy tendon accumulates damage, and then how the intrinsic and extrinsic compartments activate and coordinate tissue remodeling [18,[21][22][23]. Only slightly more is known about this process after acute injury, however studies using animal models of acute injury and repair are beginning to shed some light [53,54].…”
Section: Tendon Damage and Repair: Intrinsic Microdamage Vs Damage Cmentioning
confidence: 99%
“…The tendon core consists of densely packed Type-I collagen matrix and the fibroblastic cells that maintain it [50]. Although increasingly realized to have distinct functions in the context of tendon disease and repair, the physiological roles of many of the cells within both compartments and possible communication between the compartments is still poorly understood [50][51][52][53][54]. We proceed by outlining what is known about the intrinsic compartment that Fig.…”
Section: The Tendon Proper Its Composition and Structurementioning
confidence: 99%
“…However, the healing of tissues in which the fibers are highly organized can be challenging, as the injury site is generally poorly organized, comprising less dense and disorganized collagen . In most cases, poor healing will lead to reduced mechanical properties of the tissue, and an inability to withstand high forces, either reinjuring the same site, or even inducing a second injury …”
Section: Introductionmentioning
confidence: 99%